2014
DOI: 10.1080/17451000.2013.815781
|View full text |Cite
|
Sign up to set email alerts
|

Variability inCalanusspp. abundance on fine- to mesoscales in an Arctic fjord: implications for little auk feeding

Abstract: We studied the abundance of calanoid copepods of the genus Calanus in a high-resolution sampling grid located in the vicinity of a breeding colony of an avian Calanus predator, the little auk (Alle alle) in an Arctic fjord (Isfjorden, Svalbard) in July 2007. Within diving reach of little auks, all copepodite stages of C. finmarchicus, as well as stages CIIIÁCV of C. glacialis, were recorded in all 26 stations sampled. Spatial autocorrelation analysis was used to detect spatial heterogeneity (patches) in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
5
21
0
Order By: Relevance
“…According to Pinca & Huntley (2000), patches of this size are considered small. However, Vogedes et al (2014) found that in Svalbard fjord the zooplankton patches can be even smaller (1.2 km). In contrast, patches of large size are known to spread horizontally over many kilometres, that is between 30 and 60 km (Huntley et al 1995) or even >100 km in case of the largest patches (Pinca & Huntley 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Pinca & Huntley (2000), patches of this size are considered small. However, Vogedes et al (2014) found that in Svalbard fjord the zooplankton patches can be even smaller (1.2 km). In contrast, patches of large size are known to spread horizontally over many kilometres, that is between 30 and 60 km (Huntley et al 1995) or even >100 km in case of the largest patches (Pinca & Huntley 2000).…”
Section: Discussionmentioning
confidence: 99%
“…by net sampling (Wiebe 1970, Vogedes et al 2014, continuous water pumping (Piontkovski et al 1997, Molinero et al 2008, acoustics (Zhou & Huntley 1996, Genin et al 2005, optical counters (Basedow et al 2006, Trudnowska et al 2012, video recording (Benfield et al 1996, laboratory experiments (Dagg 1977) or modelling (Riley 1976, Woodson et al 2005. Nevertheless, this phenomenon remains more a topic of speculation than one of actual measurements and documentation.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…Despite the differences in hydrography, the abundance of Arctic holoplankton was comparable along the WSS and was in the same range as that reported in previous studies (Scott et al 2002;Kwasniewski et al 2003Kwasniewski et al , 2010Basedow et al 2004;Hop et al 2006;Weydmann and Kwasniewski. 2008;Piwosz et al 2009;Vogedes et al 2014). Thus, it seems that in 2007, the west Spitsbergen fjords still contained reservoirs of cold ArW in the bottom layers or in basins separated by sills, offering refugia for Arctic species (Arnkvaern et al 2005;Weydmann and Kwasniewski 2008) and making it possible for Arctic C. glacialis to survive in the face of climate warming.…”
Section: Discussionmentioning
confidence: 99%
“…Little auks avoid areas with turbid water and/or with high abundance of small-sized copepods (e.g. Calanus finmarchicus) making selection of their staple prey (C. glacialis) difficult Vogedes et al 2014). Kittiwakes feeding efficiently on the surface of the water, including Bbrown zones^, seem not to be affected by this problem.…”
Section: Foraging Community Structure and Habitat Preferencesmentioning
confidence: 99%